2020
DOI: 10.1371/journal.pone.0236377
|View full text |Cite
|
Sign up to set email alerts
|

Pro-atrial natriuretic peptide and pro-adrenomedullin before cardiac surgery in children. Can we predict the future?

Abstract: Introduction and objective Pro-atrial natriuretic peptide (proANP) and pro-adrenomedullin (proADM) levels increase in acute heart failure and sepsis. After cardiac surgery, children may require increased support in the intensive care unit and may develop complications. The aim of this study was to evaluate the utility of proANP and proADM values, determined prior to cardiac surgery, for predicting the need for increased respiratory or inotropic support during the post-operative period. Methods This was a prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Pro-ANP and MR-proADM levels before cardiac surgery were also higher in those patients with an increased need for ventilatory and inotropic support after the surgical intervention. The AUC for pro-ANP was greater than that of MR-proADM, but without significant differences for both cases; however, in the multivariate analysis, the only biomarker kept as an independent predictor was pro-ANP [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pro-ANP and MR-proADM levels before cardiac surgery were also higher in those patients with an increased need for ventilatory and inotropic support after the surgical intervention. The AUC for pro-ANP was greater than that of MR-proADM, but without significant differences for both cases; however, in the multivariate analysis, the only biomarker kept as an independent predictor was pro-ANP [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies show that as patients received treatment and their NYHA score improved, their atrial naturetic peptide assay level reduced in keeping with similar studies focusing on brain naturetic peptide. [48][49][50][51] Atrial naturetic peptide values were found to be highest amongst children with cardiomyopathy compared to CHD. 50 When atrial naturetic peptide and brain naturetic peptide are compared directly in assessment of paediatric heart failure, the changes noted in brain naturetic peptide/NT-proBNP are reflected by atrial naturetic peptide/MR-proANP.…”
Section: Atrial Naturetic Peptidementioning
confidence: 99%
“…9 The assessment of cardiovascular disease prognosis and procedural outcomes highlighted several parameters and biomarkers. [10][11][12][13][14][15] Many of them, including interleukins, microribonucleic acids (microRNAs), tumor necrosis factor alpha (TNF-α), and platelet-leukocyte aggregates, 16,17 have high prognostic value. However, using such markers in clinical practice is not possible, as a profound analysis of inflammatory phenomena is challenging and not costeffective.…”
Section: Introductionmentioning
confidence: 99%